Соціальна робота з підтримки інтелектуальної активності людей похилого віку - Романова, Інна (НТУ "ХПІ", 2018)
В статті розглядаються психологічні чинники сповільнення процесу старіння літніх людей; визначаються пріоритетні напрями здійснення соціальної роботи з підтримки інтелектуальної активності людей похилого віку; аналізується сучасна практика здійснення соціальної роботи з підтримки інтелектуальної активності людей похилого віку в соціальних інституціях України.

In the article there are considered the psychological factors of deceleration the aging process of elderly people; the priority directions of implementation of social work on maintenance of intellectual activity of the elderly people are determined; the current practice of social work on maintaining intellectual activity of elderly people in social institutions of Ukraine is analyzed.
Social work for supporting intellectual activity of elderly people
Keywords: когнітивний резерв; освіта літніх людей; університети третього віку; інтелектуальне волонтерство; social work; elderly people; intellectual activity; cognitive reserve; education of the elderly; university of the third age; intellectual volunteering